Performance of Leucaena leucocephala - Chaturvedi, A. N. (Indian Forester, 1983)
Leucaena eucdcephala which has been widely publicised as hily productive plantation species in all types of soils in India grows well only on deep fertile soils with adequate irrigation. It fruits within one year or planting. The tree suffers from gummosis. In comparative trials several other species have been found to grow better than Leucaena leucocephaia.